Study guide for LPIC-2 exams 201 and 202 : prepare for the Linux Professional Institute 201 and 202 exams - Meister, John E.; Safari eBooks ([Place of publication not identified] : O'Reilly, 2016)
"Linux power users who want to become Linux system administrators, junior level Linux administrators seeking to learn more about their trade, and especially those individuals studying to pass the LPIC-2 Certification exams will appreciate this comprehensive overview of Linux systems administration. Linux master John Meister draws from his twenty-five years of real world experience - working scripts and configuration files, and including, as he puts it: "some of the dumb things I've done" - to provide a detailed examination of the day-to-day tasks and decision-making performed by senior level Linux system administrators."--Resource description page.
Title from resource title screen (Safari, viewed July 22, 2016).
Presenter, John E. Meister.
Keywords: Linux -- Examinations -- Study guides; Electronic data processing personnel -- Certification; Electronic books